Early switch of Intravenous to oral antibiotics in uncomplicated Enterobacteriaceae Bacteremia - a single centre experience - Ismail, Izzad Emir; Kori, Najma; Cheong, Xiong Khee; Lau, Chee Lan; Ramli, Ramliza; Hod, Rozita; Zainulabid, Ummu Afeera; Periyasamy, Petrick (Universiti Kebangsaan Malaysia, 2024)
Enterobacteriaceae bloodstream infections pose significant clinical challenges, necessitating prompt effective antimicrobial therapy. This prospective study aims to evaluate the efficacy and safety of early switch therapy (EST) from intravenous(IV) to oral antibiotics in uncomplicated Enterobacteriaceae bacteremia. A total of 51 patients were studied over a year in a tertiary teaching hospital. Patients who met predetermined criteria for clinical stability after 72 hours of IV antibiotics were recruited. Primary outcome was a 30-day relapse rate after completing therapy. Secondary outcomes were 30-day mortality, readmission, and hospital stays. In this study, all eligible patients (100%) successfully switched to oral antibiotics without recurrence. The readmission rate was 7.8%, none related to bacteremia, with 2% mortality due to unrelated causes. In total, 66.7% of patients had hospital stays of less than five days. Escherichia coli was the most prevalent cause of bacteremia, accounting for 70.6% and 35.3% of urinary tract infections. In conclusion, this is the first Malaysian study on early switching to oral antibiotics in uncomplicated Enterobacteriaceae bacteremia. It demonstrates the feasibility and safety of early switch oral antibiotics, with positive results and no relapses. These findings lend support to the potential benefits of antimicrobial stewardship methods that aim to reduce IV antibiotic use while optimising oral therapy in selected patients. Futureresearch, including randomised trials, is essential to establish evidence-based guidelines for treating uncomplicated Enterobacteriaceae bacteremia.